Assessing Soil Pollution with Heavy Metals using Contamination Factor Index at Zahedan Municipal Landfill - Fatemeh Bazzi; Mohammad Reza Rezaei; Mohammad Hossein Sayadi Anari (محیط زیست و مهندسی آب, 2017)
Solid waste is one of the most important sources of soil contamination. Soil chemical contaminants such as heavy metals have created deep concern throughout the world. Heavy metals are naturally present in all soils, but soil contamination due to human activities is increasing. The accumulation of these metals in the soil eventually results in their entry into the food cycle and threaten human health and other living beings. In this study, the soil pollution of Zahedan city landfill by heavy metals was studied using contamination factor index. A total of 20 soil samples, 10 topsoil samples (up to 30 cm) and 10 depth soil samples (from a depth of 30 to 60 cm) were collected from landfill and processed for determination of element concentrations by Atomic Absorption Spectrometry and for statistical analysis, the SPSS software version 23 was used. The results showed that mean concentrations of chromium, cadmium, lead, and arsenic in topsoil were 152.48, 0.213, 54.499, and 0.344 mg/kg respectively while these concentrations for deep soil were 177.14, 0.252, 49.365, 0.414 mg/kg respectively. The contamination factor index confirmed that most of sample stations were in class of low (CF >1 and 1 15â‰¤">  CF >3) to moderate pollution.